2022
DOI: 10.3390/brainsci12070851
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Radiomics for Diagnosis of Parkinson’s Disease

Abstract: Background: Diagnosis of Parkinson’s Disease (PD) based on clinical symptoms and scale scores is mostly objective, and the accuracy of neuroimaging for PD diagnosis remains controversial. This study aims to introduce a radiomic tool to improve the sensitivity and specificity of diagnosis based on Diffusion Tensor Imaging (DTI) metrics. Methods: In this machine learning-based retrospective study, we collected basic clinical information and DTI images from 54 healthy controls (HCs) and 56 PD patients. Among them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Following the exclusion of 121 duplicate studies, 43 studies were screened based on their titles or abstracts. Ultimately, a total of 28 articles ( Cheng et al, 2019 ; Shinde et al, 2019 ; Wu et al, 2019 ; Xiao et al, 2019 ; Cao et al, 2020 , 2021 ; Liu et al, 2020 ; Pang et al, 2020 , 2022 ; Shu et al, 2020 ; Dhinagar et al, 2021 ; Hu et al, 2021 ; Li et al, 2021 , 2022 ; Ren et al, 2021 ; Shi et al, 2021 , 2022a , 2022b ; Sun et al, 2021 , 2022 ; Tupe-Waghmare et al, 2021 ; Zhang et al, 2021 ; Ben Bashat et al, 2022 ; Guan et al, 2022 ; Kang et al, 2022 ; Kim et al, 2022 ; Shiiba et al, 2022 ; Zhao et al, 2022 ) were deemed eligible and included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the exclusion of 121 duplicate studies, 43 studies were screened based on their titles or abstracts. Ultimately, a total of 28 articles ( Cheng et al, 2019 ; Shinde et al, 2019 ; Wu et al, 2019 ; Xiao et al, 2019 ; Cao et al, 2020 , 2021 ; Liu et al, 2020 ; Pang et al, 2020 , 2022 ; Shu et al, 2020 ; Dhinagar et al, 2021 ; Hu et al, 2021 ; Li et al, 2021 , 2022 ; Ren et al, 2021 ; Shi et al, 2021 , 2022a , 2022b ; Sun et al, 2021 , 2022 ; Tupe-Waghmare et al, 2021 ; Zhang et al, 2021 ; Ben Bashat et al, 2022 ; Guan et al, 2022 ; Kang et al, 2022 ; Kim et al, 2022 ; Shiiba et al, 2022 ; Zhao et al, 2022 ) were deemed eligible and included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included in this research are shown in Table 1 and Supplementary Table 4 . The original 28 studies were published between 2019 and 2022, with 27 of them from Asia ( Cheng et al, 2019 ; Shinde et al, 2019 ; Wu et al, 2019 ; Xiao et al, 2019 ; Cao et al, 2020 , 2021 ; Liu et al, 2020 ; Pang et al, 2020 , 2022 ; Shu et al, 2020 ; Hu et al, 2021 ; Li et al, 2021 , 2022 ; Ren et al, 2021 ; Shi et al, 2021 , 2022a , 2022b ; Sun et al, 2021 , 2022 ; Tupe-Waghmare et al, 2021 ; Zhang et al, 2021 ; Ben Bashat et al, 2022 ; Guan et al, 2022 ; Kang et al, 2022 ; Kim et al, 2022 ; Shiiba et al, 2022 ; Zhao et al, 2022 ) and one from North America ( Dhinagar et al, 2021 ). The study comprised a total of 6,057 participants, with 3,422 patients diagnosed with PD, 1,983 healthy controls, and 652 cases of APS (476 with MSA and 176 with PSP).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DKI has been repeatedly applied in PwPD. The most recent and comprehensive systematic review and meta-analysis of DKI imaging in PD [93] included 14 studies with 535 PwPD and 486 HCs. Besides some methodological heterogeneity, extensive alterations, e.g., of subcortical DKI metrics, have been observed [93].…”
Section: Diffusion Kurtosis Imagingmentioning
confidence: 99%